Direct nanoscale observations of the coupled dissolution of calcite and dolomite and the precipitation of gypsum - Offeddu, F.; Cama, J.; Soler, J.; Putnis, Christine (2014)
In-situ atomic force microscopy (AFM) experiments were performed to study the overall process of dissolution of common carbonate minerals (calcite and dolomite) and precipitation of gypsum in Na2SO4 and CaSO4 solutions with pH values ranging from 2 to 6 at room temperature (23 ± 1 °C). The dissolution of the carbonate minerals took place at the (104) cleavage surfaces in sulfate-rich solutions undersaturated with respect to gypsum, by the formation of characteristic rhombohedral-shaped etch pits. Rounding of the etch pit corners was observed as solutions approached close-to-equilibrium conditions with respect to calcite. The calculated dissolution rates of calcite at pH 4.8 and 5.6 agreed with the values reported in the literature. When using solutions previously equilibrated with respect to gypsum, gypsum precipitation coupled with calcite dissolution showed short gypsum nucleation induction times. The gypsum precipitate quickly coated the calcite surface, forming arrow-like forms parallel to the crystallographic orientations of the calcite etch pits. Gypsum precipitation coupled with dolomite dissolution was slower than that of calcite, indicating the dissolution rate to be the rate-controlling step. The resulting gypsum coating partially covered the surface during the experimental duration of a few hours.